2022
DOI: 10.3389/fcvm.2022.880374
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Women: A South-Asian Perspective

Abstract: IntroductionHypertension is an important contributor to cardiovascular disease related morbidity and mortality. Despite the magnitude of its negative impact on cardiovascular outcomes, treatment and control of hypertension remain suboptimal in both men and women.Materials and MethodsNumerous databases, i.e., PubMed, ScienceDirect, etc., were searched using keywords to identify relevant studies to our narrative review. The findings from the most pertinent articles were summarized and integrated into our narrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 145 publications
0
1
0
Order By: Relevance
“…[270][271][272][273][274] Analysis of data from the National Family Health Survey 4, Study of Ageing and Health Wave 2 datasets (NFHS-SAGE), and the Longitudinal Ageing Study of India (LASI) dataset revealed a distinct trend: males demonstrated a higher prevalence of hypertension until the age of 50, after which females exhibited higher rates. 275 Based on the WHO-SAGE study, hypertension was more prevalent in tribals, poor, Sikhs, and older women. 276 Child brides and adolescent mothers have been reported to be more likely to have hypertension later in life.…”
Section: -Hypertension In Womenmentioning
confidence: 99%
“…[270][271][272][273][274] Analysis of data from the National Family Health Survey 4, Study of Ageing and Health Wave 2 datasets (NFHS-SAGE), and the Longitudinal Ageing Study of India (LASI) dataset revealed a distinct trend: males demonstrated a higher prevalence of hypertension until the age of 50, after which females exhibited higher rates. 275 Based on the WHO-SAGE study, hypertension was more prevalent in tribals, poor, Sikhs, and older women. 276 Child brides and adolescent mothers have been reported to be more likely to have hypertension later in life.…”
Section: -Hypertension In Womenmentioning
confidence: 99%
“…Male individuals develop cardiovascular diseases attributable to endothelial dysfunction earlier and more frequently than women. This difference between the two sexes persists until menopause, when endothelial dysfunction has a slightly higher incidence in women than in men [ 34 , 35 ]. The decline in female sex hormones, especially estrogen, and the negative effect of androgens are the factors that underlie the loss of the protection enjoyed by women of childbearing age.…”
Section: Effect Of Sex Hormone Differences On Endothelial Functionmentioning
confidence: 99%